Supplementation with MitoTEMPO before cryopreservation improves sperm quality and fertility potential of Piedmontese beef bull semen - Elkhawagah, Ahmed R.; Ricci, Alessandro; Bertero, Alessia; Poletto, Mariagrazia Lucia; Nervo, Tiziana; Donato, Gian Guido; Vincenti, Leila; Martino, Nicola Antonio (Frontiers in Veterinary Science, 2024)
The purpose of this study was to improve the quality of frozen–thawed Piedmontese bull semen by incorporating MitoTEMPO (MT) in extended semen before cryopreservation. Semen was collected from 4 fertile bulls, using an artificial vagina, once weekly for 6 consecutive weeks. Semen samples were pooled, diluted with Bullxcell® extender, and supplemented with different concentrations of MT (0 as control, 5, 10, 20, 40, and 80 μM) before cooling, equilibration, and freezing procedures. The frozen–thawed semen was assessed for motility, vitality, acrosome intactness, plasma membrane integrity, DNA integrity, apoptosis, mitochondrial membrane potential, intracellular ROS level and in vitro fertilizing capability. The results showed that MT at concentrations of 10, 20, and 40 μM improved the total, progressive, and rapid motility directly after thawing while, at the highest tested concentration (80 μM), it decreased the progressive and rapid motility after 1, 2, and 3 h of incubation. The sperm kinetics including STR and LIN were noticeably increased at concentrations of 10, 20, and 40 μM directly after thawing (0 h), whereas the MT effect was variable on the other sperm kinetics during the different incubation periods. MitoTEMPO improved the sperm vitality at all tested concentrations, while the acrosomal and DNA integrity were improved at 20 μM and the mitochondrial membrane potentials was increased at 80 μM. The cleavage and blastocyst formation rates were significantly increased by using semen treated with 20 μM MT compared with controls. These findings suggest a potential use of MT mainly at a concentration of 20 μM as an additive in the cryopreservation media of bull semen to improve sperm quality.